MUTATION IN VIRUS AND GENETIC ALTERATION IN VIRUSES - A REVIEW - P, Yazhlini; N.P, Muralidharan.; Somasundaram, Jayalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
The remarkable capacity of some viruses to adjust and adapt to a new host and environment is highly dependent on the capacity to generate de Novo diversity in a short period. Rates of spontaneous mutation shift abundantly among viruses. RNA viruses change quicker than DNA viruses, single-stranded virus transforms quicker than double standard infection and genome size seems to connect adversely with transformation rate. Viral change rates are equalized at various stages, like polymerase fidelity, Sequence content, template secondary structure, cellular microenvironment, application mechanism, proofreading and post replication repair. The mutation rate of an organism is defined as the probability where a change in genetic information is passed to the next generation. In viruses, a generation is often defined as a cell infection cycle, which includes an attachment to the cell surface, entry, gene expression, replication, encapsidation, and release of infectious particles. Also, enormous quantities of changes can be presented by some virus-encoded diversity generating elements, as well as by host-encoded cystine/ adenosine deaminase. Our recent knowledge on viral change rates explains that viral hereditary variety is determined by multiple viruses and host interaction and the viral mutation rates can evolve in response to specific selective pressures.